The accessibility of Kansas State University's campus: A community-based action research project - Wilkinson, Kayla; McAfee, Sara; Riordan, Melanie; Davis, Kamaron; Edwards, Samuel (Kansas State University. K-State Libraries, 2015)
For our Culture and Context in Leadership class we were challenged to conduct research regarding inclusion in the Kansas State or Manhattan communities. Our group chose to look at the accessibility of Kansas State University's campus for physically disabled students, staff, and visitors. While working with our community partner, the Student Access Center, we discovered that there was no map of campus showing accessible routes and entrances. We decided to create such a map that the SAC and new student services would be able to utilize. In order to get reliable information, we analyzed several buildings looking for accessibility issues. We each completed an ethnography to get a first person point of view as well as interviews with K-State Students who deal with this everyday.
Citation: Wilkinson, K., McAfee, S., Riordan, M., Davis, K., & Edwards, S. (2015). The accessibility of Kansas State University's campus: A community-based action research project. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Campus; MapPhysical disabilities; Kansas State University; Leadership; Inclusion; Culture